ISLAM DI THAILAND - Rusli Rusli (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
The development of Islamic education in Thailand shows a very dynamic graph. Although Thailand is not a predominantly Muslim country and a non-Muslim country. This is seen from the beginning has been established educational al-quran famous for cottage education, and its alumni very important role in the middle of society. Besides, there are also madrasah and higher education schools that are not much different from Islamic education in Indonesia. But in the social order of Muslims is less well received, because it is considered as a foreigner/guests/khaek who sometimes get poor treatment.